Rutting Performance of Hot Mix Asphalt Created Using Both Traditional Superpave Procedure and Bailey Techniques - Kamal, Ali; Al-Mosawe, Hasan; Nassar, Ahmed I. M. (Al-Nahrain Journal for Engineering Sciences, 2025)
The present investigation looked at whether the Bailey approach to aggregate gradation could be used to construct Superpave HMA blends. It also looked at how this approach influenced the rutting performance associated with these mixes and compared it to mixes of asphalt created by Superpave gradations. The current research included four aggregate gradations: both fine and coarse gradations for the Superpave and Bailey gradation procedures. The repeated loading test was utilized to assess the rutting performance. The findings indicated that temperature, stress level, and aggregate gradation all had a significant impact on rutting performance. In contrast to the other three gradations, the third mixture gradation exhibited the least amount of non-reversible deformation. It translates to pavement that is more resistant to rutting and less susceptible to it.